High-Intensity Cardiac Rehabilitation Training of a Commercial Pilot Who, After Percutaneous Coronary Intervention, Wanted to Continue Participating in a Rigorous Strength and Conditioning Program. Issue 1 (1st January 2016) - Shrestha, Sanjay; Adams, Jenny; Lawrence, Anne; Schussler, Jeffrey M.
Abstract : After undergoing elective percutaneous coronary intervention, a 64-year-old commercial pilot was referred to cardiac rehabilitation. His stated goals were to continue participating in a rigorous strength and conditioning program at a community workout facility and to resume working as a pilot. To help him meet those goals, we designed and implemented a regimen of high-intensity exercises, with quick transitions between a variety of tasks that are not typically included in cardiac rehabilitation programs (e.g., medicine ball throws, push-ups, dead lifts, squats, military presses, sprints, and lunges). The training was symptom limited, enabling the patient to reach extreme levels of physical exertion in a controlled, monitored setting. By studying his training data (heart rate, blood pressure, and rating of perceived exertion), we were able to give him specific recommendations for controlling his exercise intensity after graduating from our program. More than 18 months later, he continues to exercise vigorously 3 days per week and is working as a commercial pilot.